1992
DOI: 10.1111/j.1740-8261.1992.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Determination of Renal Volume in the Dog

Abstract: Ultrasonographic linear and area measurements were performed on both kidneys of 15 clinically healthy dogs. Renal volumes were calculated from linear and area data applying three prolate ellipsoid models. Ultrasonographic volumes were then compared using linear regression analysis with kidney volumes measured in vitro by water displacement. In vivo ultrasonographic volumes had a statistically significant relationship with the in vitro volume. The highest correlation was provided by the single plane area method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 15 publications
2
27
1
5
Order By: Relevance
“…This results in the imaging of imprecise organ margins (Walter et al, 1987) and failure to image the kidney in its greatest dimension (Rosenbaum et al, 1978). Felkai et al, (1992) observed that it was occasionally difficult to define the renal border at the hilus, probably because of presence of connective tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the imaging of imprecise organ margins (Walter et al, 1987) and failure to image the kidney in its greatest dimension (Rosenbaum et al, 1978). Felkai et al, (1992) observed that it was occasionally difficult to define the renal border at the hilus, probably because of presence of connective tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The cortex and medullary thickness were also increased linearly in both the kidney. Felkai et al (1992) considered that the variation in the various renal parameters occurs due to limited visual acuity of the observer while observing an ultrasonogram. This results in the imaging of imprecise organ margins (Walter et al, 1987) and failure to image the kidney in its greatest dimension (Rosenbaum et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…59 In dogs, ultrasound is clinically useful for determining kidney size, with measurement in multiple planes producing an estimated renal volume that correlates well to actual renal size. [60][61][62][63] Potential inaccuracies in ultrasonographic evaluation of feline kidneys include observer visual error, imprecise border definition due to minimal capsular echo, and ultrasonographic artifacts. 64 On ultrasound the renal cortex is uniform and is hyperechoic compared to the spleen in the normal cat.…”
Section: D: Methods Of Assessing Renal Morphologymentioning
confidence: 99%
“…Alterações no formato e tamanho dos rins comumente ocorrem como resultado de muitas enfermidades renais e a detecção destas mudanças são importantes para o diagnóstico e prognóstico das renopatias (Felkai et al 1992). As mudanças anatômicas nos rins podem ser avaliadas pela radiografia (Finco et al 1998), laparoscopia (Nyland & Matoon 1995) e ultra-sonografia (Espada et al 2006).…”
Section: Introductionunclassified
“…Estudos correlacionando as medidas lineares e o volume renal com o peso canino tem sucesso limitado (Felkai et al 1992, Sampaio & Araújo 2002, Nyland et al 2005, uma vez que o tamanho do órgão pode ser superestimado em um cão adulto subnutrido, assim como subestimado em cães adultos obesos. Recentemente, temse buscado correlacionar o diâmetro longitudinal do rim com o diâmetro da artéria aorta abdominal em cães clinicamente normais, com intuito de estabelecer parâmetro de normalidade para o tamanho renal (Mareschal et al 2007).…”
Section: Introductionunclassified